Iman yang Bereaksi: Kerja Bakti Rukun Tetangga 07 Dusun/ Desa Pusat Damai sebagai Wujud Nyata Pelayanan Kasih dalam Pendidikan Agama Kristen - Marthen Mau (Lembaga Pengembangan Kinerja Dosen, 2026)
Community service in the neighborhood association (RT) of 07 Dusun/Village Pusat Damai is a concrete manifestation of loving service in Christian religious education. Sometimes, certain individuals in the neighborhood association (RT) are not directly involved in community service activities due to age and busy schedules. People who are not directly involved in community service activities indicate that their faith has not yet been expressed through concrete actions. The purpose of this community service research is to ensure that each person's faith is expressed through concrete actions in the neighborhood association (RT) as a form of loving service in Christian religious education. To produce good community service research, a qualitative research method is required through literature and documentation. The results found through this community service research are that faith that is expressed can be realized through community service carried out by all residents of RT 07 Dusun/Village Pusat Damai, demonstrating a high level of enthusiasm. This community service research can be concluded that every believer must have faith that is expressed through concrete actions, namely community service in the neighborhood, to be further enhanced in the future.